Caracterização química e resistência à flexão de uma resina acrílica após a incorporação de um polímero com atividade antimicrobiana - Rodriguez, Larissa Santana [UNESP]; Paleari, André Gustavo [UNESP]; Oliveira Júnior, Norberto Martins de [UNESP]; Marra, Juliê; Pero, Ana Carolina [UNESP]; Compagnoni, Marco Antonio [UNESP] (My University, 2011)
Introduction: Acrylic resins with antimicrobial activity could offer patients complete denture and partial wearers’ improvement in their oral health by means of a better control of biofilm formation. Objective: The objective of this study was chemically characterize a denture base acrylic resin (Onda-Cryl) that was incorporated the antimicrobial polymer 2-tert-butylaminoethyl (PTBAEMA) and to evaluate the flexural strength of this resin. Material and method: Rectangular specimens were from a denture base acrylic resin with different concentrations of PTBAEMA (0,5 and 10%). Specimens’ surfaces were assessed by ESCA to detect the presence of amine groups, represented by nitrogen ratios. Analysis of FTIR and DSC were used to evaluate the polymerization process and the influence of the incorporation of PTBAEMA in Tg of the resin, respectively. Flexural strength was evaluated and the results were analyzed by ANOVA/Tukey HSD test (α = 0.05). Result: Different nitrogen ratios were observed for groups 0, 5 and 10% (0, 0.85 and 5.82% respectively), there was copolymerization between the resin and PTBAEMA, and reduction of Tg after incorporation of PTBAEMA. Significant differences were found for flexural strength (p < 0.05), the mean values were 94.7 ± 9.4A, 21.8 ± 3.4B, 13.0 ± 1.5C MPa for groups 0,5 and 10%, respectively. Conclusion: The incorporation of PTBAEMA resulted in copolymerization, presence of amine groups on specimens’ surfaces, and in decrease of Tg and flexural strength.

Introdução: Resinas acrílicas com atividade antimicrobiana poderiam oferecer aos pacientes usuários de próteses parciais e totais melhorias na sua saúde oral por meio de um melhor controle de biofilme. Objetivo: O objetivo deste estudo foi caracterizar quimicamente uma resina acrílica para base protética (Onda-Cryl), à qual foi incorporado o polímero antimicrobiano 2-tert-butilaminoetil (PTBAEMA), além de avaliar a resistência à flexão dessa resina. Material e método: Foram confeccionados espécimes de formato retangular a partir da resina acrílica contendo diferentes concentrações de PTBAEMA (0,5 e 10%). A superfície dos espécimes foi avaliada por meio de ESCA para detectar a presença de grupos amina, representada por índices de nitrogênio. As análises de FTIR e DSC foram utilizadas para avaliar o processo de polimerização e a influência da incorporação de PTBAEMA na Tg da resina, respectivamente. A resistência à flexão dos espécimes foi avaliada e os resultados foram analisados por meio de análise de variância a um fator (ANOVA), seguida pelo teste HSD de Tukey (α = 0,05). Resultado: Foram observados diferentes índices de nitrogênio para os grupos 0, 5 e 10% (0, 0,85 e 5,82%, respectivamente); houve copolimerização entre a resina e o PTBAEMA, e redução da Tg após incorporação. Foram encontradas diferenças significantes para a resistência à flexão (p < 0,05) cujos resultados foram 94,7 ± 9,4A, 21,8 ± 3,4B, 13,0 ± 1,5C MPa para os grupos 0,5 e 10%, respectivamente. Conclusão: A incorporação de PTBAEMA resultou em copolimerização, presença de grupos amina na superfície dos espécimes e diminuição da Tg e da resistência à flexão.
Chemical characterization and flexural strength of an acrylic resin after the incorporation of a polymer with antimicrobial activity
Keywords: Denture; Acrylic resins; Antimicrobial agents; Prótese total; Resinas acrílicas; Agentes antimicrobianos